2009
DOI: 10.1002/app.31141
|View full text |Cite
|
Sign up to set email alerts
|

Value‐added derivatives of soda lignin from alfa grass (Stipa tenacissima). I. Modification and characterization

Abstract: Attention deficit hyperactivity disorder (ADHD) is the most common behavioral disorder in childhood, and often has effects detectable into adulthood. Advances in genetic linkage and association analysis have begun to elucidate some of the genetic factors underlying this complex disorder. Recently, we identified LPHN3, a novel ADHD susceptibility gene harbored in 4q, and showed that a LPHN3 common haplotype confers susceptibility to ADHD and predicts effectiveness of stimulant medication. Here we present the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 47 publications
1
17
0
2
Order By: Relevance
“…The residual lignin molecular weight decreasedi nb oth cases relative to that of the corresponding untreated lignins, which provedt hat depolymerization had occurred.R iedl et al and Chakar and Ragauskas reported that during the degradation process, repolymerization (condensation) of lignin with active intermediates such as quinone methide and other radical phenolic speciesg enerated modified ChemSusChem 2016, 9,3220 -3229 www.chemsuschem.org structures with higherm olecular weights than the initial compounds. [22,25] The decreased molecular weight of residue lignin in our case suggests that W 2 Cw ould not induce as evere repolymerization reaction,w hich is one of the advantages of this catalytic system.…”
Section: Conversion Of Realistic Lignin Feedstocksmentioning
confidence: 78%
See 2 more Smart Citations
“…The residual lignin molecular weight decreasedi nb oth cases relative to that of the corresponding untreated lignins, which provedt hat depolymerization had occurred.R iedl et al and Chakar and Ragauskas reported that during the degradation process, repolymerization (condensation) of lignin with active intermediates such as quinone methide and other radical phenolic speciesg enerated modified ChemSusChem 2016, 9,3220 -3229 www.chemsuschem.org structures with higherm olecular weights than the initial compounds. [22,25] The decreased molecular weight of residue lignin in our case suggests that W 2 Cw ould not induce as evere repolymerization reaction,w hich is one of the advantages of this catalytic system.…”
Section: Conversion Of Realistic Lignin Feedstocksmentioning
confidence: 78%
“…[22,25] The decreased molecular weight of residue lignin in our case suggests that W 2 Cw ould not induce as evere repolymerization reaction,w hich is one of the advantages of this catalytic system. The residual lignin molecular weight decreasedi nb oth cases relative to that of the corresponding untreated lignins, which provedt hat depolymerization had occurred.R iedl et al and Chakar and Ragauskas reported that during the degradation process, repolymerization (condensation) of lignin with active intermediates such as quinone methide and other radical phenolic speciesg enerated modified www.chemsuschem.org structures with higherm olecular weights than the initial compounds.…”
Section: Conversion Of Realistic Lignin Feedstocksmentioning
confidence: 78%
See 1 more Smart Citation
“…For example, 2‐(2,6‐dimethoxyphenoxy)‐1‐phenylethanol with two methoxy groups (substrate 3 in Table ), a typical syringyl unit, is a predominant moiety in birch lignin . 2‐Phenoxy‐1‐phenylethanol (Table , substrate 2 ), without methoxy substitution on the phenyl ring is a component of grass lignin . All the investigated substrates provided 2‐phenylethanol and phenol derivatives (compounds a and b in Table ) as the major products, suggesting that the aryl C−O bonds of the substrates were selectively cleaved with the aryl rings intact.…”
Section: Methodsmentioning
confidence: 99%
“…Lignin was isolated by acid precipitation from an industrial black liquor obtained from the soda pulping of bagasse (supplied by Nanning Sugar Industry Co., Ltd. China), and the isolated method was carried out as described by Nadji et al (2010). The black liquor was filtered prior to acidulation in order to remove suspended solid residues.…”
Section: Methodsmentioning
confidence: 99%